Literature and sustainability Exploratory essays - Johns-Putra, Adeline (Manchester University Press, 2017)
Sustainability has become a key socio-political issue over recent years. However, whilst the literary-critical community has advanced enthusiastically on an exciting range of environmentally-based analyses (most obviously through the work of ecocriticism), its response specifically to sustainability-as an attempt to reconceptualise the way we live, as an idea with a particular history, and as a ubiquitous term driven through over-use to near meaninglessness-has been extremely limited. The basic idea of the volume is to make a start on filling this gap. Split into four sections: Historicising sustainability, Discourses of sustainability, The sustainability of literature, Sustainability in literature - it has some very good contributors, and starts off with an introduction about the history of the term, looks at its beginnings in the C19th, and goes onto show how contemporary authors are dealing with it including Jeanette Winterson, Michel Houellebecq, Margaret Atwood and Amitav Ghosh.